Different Proliferation Patterns in Breast Cancer: AgNOR Measurements in ER-Negative and ER-Positive Tumor Cells - Lukas Günther; Peter Hufnagl; Klaus‐Jürgen Winzer; Hans Guski (Analytical Cellular Pathology)
The relation between estrogen receptors (ER) and argyrophilic nucleolar organizer regions (AgNORs) in situ within human breast cancer cells was analyzed. For AgNOR measurements in 49 invasive breast carcinomas, a new reproducible staining method for dual demonstration of ER and AgNORs was applied. Quantitative AgNOR variables were determined in ER‐positive and ER‐negative tumor cells by digital image analysis. The relationships between AgNOR parameters of ER‐positive and ER‐negative cells and other prognostic factors of breast cancer [Bloom–Richardson‐Grading and growth fraction (Ki‐67 index)] were investigated. A higher AgNOR content in ER‐negative cells and a special clustering phenomenon in ER‐positive tumor cells were found. Correlation with other criteria of malignant potential could be exclusively demonstrated for ER‐negative cells. ER‐negative cells of breast cancer can be characterized as the more malignant and possibly prognosis‐dictating cell fraction. Thus, ER‐negative cells probably contribute more to the progression of the tumor disease and furthermore to the prognosis than ER‐positive cells. We recommend measurement AgNORs exclusively in ER‐negative cells of breast cancer.